2014
DOI: 10.1111/echo.12683
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography Detects Elevated Left Ventricular Filling Pressures in Heart Transplant Recipients

Abstract: Diastolic dysfunction is a recognized complication in heart transplant (HTx) recipients that limits exercise capacity and is a risk factor for mortality. We investigated the ability of echocardiography to detect elevated pulmonary capillary wedge pressure (mean PCWP>15 mmHg) in HTx recipients. This retrospective study comprised HTx recipients with echocardiography and right heart catheterization within 24 hours (n = 100, 113 investigations). Echocardiographic assessment was performed using mitral inflow (E/A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…They suggested that an elevated E/A ratio in HTR is related to reduced left atrial contractility rather than to LV diastolic dysfunction. In contrast, E/A ratio significantly correlated with catheter pulmonary capillary wedge pressure in two other studies . As we found that E/A>2 was associated with cardiac events, our study also suggests that E/A>2 is probably a sign of myocardial fibrosis and CAV of the aging graft.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…They suggested that an elevated E/A ratio in HTR is related to reduced left atrial contractility rather than to LV diastolic dysfunction. In contrast, E/A ratio significantly correlated with catheter pulmonary capillary wedge pressure in two other studies . As we found that E/A>2 was associated with cardiac events, our study also suggests that E/A>2 is probably a sign of myocardial fibrosis and CAV of the aging graft.…”
Section: Discussionsupporting
confidence: 53%
“…Consistently, among the patients of our study with E/A>2, this abnormality occurred in most cases (74%) during the first year after transplantation. Thus, in previous studies, the ability of this ratio to predict high LV filling pressures was controversial . Pascale et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though some investigators are actively trying to use parameters assessing diastolic function, but the results are con icted, especially in pediatric patients. [16][17][18][19][20][21][22][23] In this study, we pay more attention to the systolic function.…”
Section: Discussionmentioning
confidence: 99%